2021
DOI: 10.2147/jpr.s308607
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning Making Model Applied to Community-Dwelling Adults with Chronic Pain

Abstract: Purpose Chronic pain is a multidimensional experience that is influenced by biological, psychological, social, and spiritual factors. The Meaning Making Model is a recent cognitive behavioral model that has been developed to understand how psychosocial factors influence adjustment to stressful events, such as having a chronic illness. This qualitative study aims to understand the potential utility of this model for understanding the role of meaning making in adjustment to chronic pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The role of spirituality in health promoting behaviors which stimulate people's own understanding of the reality in terms of complex, intelligible, and biological processes, has been studied worldwide. 21,22 Specifically, A Saudi Arabian and Pakistani study also revealed that perceived positive health states are closely related to increased exercises, spiritual growth, and the interpersonal relations for health improving lifestyles. 8,23 In fact, the present study is an interesting representation of ties of all dimensions of spirituality and health promoting style.…”
Section: Discussionmentioning
confidence: 99%
“…The role of spirituality in health promoting behaviors which stimulate people's own understanding of the reality in terms of complex, intelligible, and biological processes, has been studied worldwide. 21,22 Specifically, A Saudi Arabian and Pakistani study also revealed that perceived positive health states are closely related to increased exercises, spiritual growth, and the interpersonal relations for health improving lifestyles. 8,23 In fact, the present study is an interesting representation of ties of all dimensions of spirituality and health promoting style.…”
Section: Discussionmentioning
confidence: 99%
“…In one example, Park and colleagues showed that when global meanings are violated due to a stressful event, these violations are associated with more PTSD symptoms through negative views of the world and self (Park et al, 2012), highlighting how potentially traumatic events may disrupt meaning-making processes related to the self and the world. Similarly, for chronic pain, Ferreira-Valente et al (2021) validated portions of Park’s meaning-making model, showing how patients with chronic pain may appraise pain as harm/threat, loss, uncontrollable, and/or a challenge. The meaning-making model posits that meaning-making processes (i.e., situational meaning) lead to meanings made that may include acceptance, changes in global beliefs, changes in global goals, alterations of identity, and changes in one’s subjective sense of meaning.…”
Section: Current Models Of Co-occurring Chronic Pain and Ptsdmentioning
confidence: 99%
“…In turn, this results in a feedback loop that then influences one’s global meaning. In Ferreira-Valente et al’s (2021) work, they found that patients used accommodation during meaning-making, wherein they altered their goals and endorsed a renewed sense of meaning in life. Just as individuals who experienced a traumatic event may need to reconcile their assumptions of a just-world with the fact they have experienced an apparently unjust trauma (Janoff-Bulman, 1992), individuals with pain also may believe they experienced an injustice from the emergence of their chronic pain (M.…”
Section: Current Models Of Co-occurring Chronic Pain and Ptsdmentioning
confidence: 99%
“…24 Personal and interpersonal processes of meaning-making involving the relation between patients' identity, agency, and social status and their suffering do not receive as much attention. 27 Both the biomedical model and the dominant version of the BPS model focus on the former mechanistic questions about “how” pain is produced and modulated rather than the latter meaning-focused “why” questions about personal reasons for pain and suffering. 84 Our contemporary interpretation of Fordyce's model challenges this separation of mechanisms and meanings and these distinct approaches to pain vs suffering.…”
Section: The Treatment Implications Of “Biology First”mentioning
confidence: 99%